PENGEMBANGAN WORKSHEET MATERI ASAM DAN BASA MENGGUNAKAN MODEL POE BERBASIS POTENSI LOKAL KALIMANTAN SELATAN (Jurnal Inovasi Pendidikan Kimia, 2019)
One of the factors that lowers the students' conceptual understanding of acid-base material is the limited learning resources in the form of worksheets. Worksheets can be developed through Predict, Observe, Explain (POE) learning models and utilize local potential in South Kalimantan. This is an effort to improve students' conceptual understanding of the material. Therefore, the purpose of this study was to develop an acid base worksheet using the local potential based POE model of South Kalimantan and find out the feasibility of the worksheet. The type of research used was research and development which adopted from the procedure of developing Borg and Gall. The object of this development research is students of class XI MIPA MAN Banjarmasin and students of Tadris Kimia UIN Antasari. The data collection technique uses a worksheet feasibility test questionnaire given to the research object. The data analysis technique uses quantitative descriptive on the results of filling out the questionnaire by the validator and research object. The research result show that the acid base worksheet using the local potential based POE model of South Kalimantan is feasible to use with a revision of 92.09%. While the results of the trials on the research object, the worksheet is classified as very good with a value of 82.78%.